2009
DOI: 10.1016/j.jaci.2009.01.049
|View full text |Cite
|
Sign up to set email alerts
|

The glucocorticoid receptor heterocomplex gene STIP1 is associated with improved lung function in asthmatic subjects treated with inhaled corticosteroids

Abstract: Background Corticosteroids exert their anti-inflammatory action by binding and activating the intracellular the glucocorticoid receptor (GR) hetero-complex. Objective Evaluate the genes HSPCB, HSPCA, STIP1, HSPA8, DNAJB1, PTGES3, FKBP5, and FKBP4 on corticosteroid response. Methods Caucasian asthmatics (382) randomized to once daily flunisolide or conventional inhaled corticosteroid therapy were genotyped. Outcome measures were baseline FEV1, % predicted FEV1, and % change in FEV1 after corticosteroid trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
3
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 33 publications
2
68
3
8
Order By: Relevance
“…Similar to our findings in bronchial brushing and biopsy specimens, inhaled budesonide treatment has previously been shown to increase FKBP5 expression in bronchial biopsy specimens of subjects with asthma (46). However, in a previous genetic association study, there was no association of genetic polymorphisms in FKBP5 with improved lung function in subjects with asthma treated with inhaled corticosteroids (47). Given its role in glucocorticoid signaling and its reproducible demonstration of induction of expression after inhaled corticosteroid treatment in subjects with asthma, FKBP5 warrants further investigation for its involvement in asthma pathogenesis and treatment response.…”
Section: Original Researchsupporting
confidence: 89%
“…Similar to our findings in bronchial brushing and biopsy specimens, inhaled budesonide treatment has previously been shown to increase FKBP5 expression in bronchial biopsy specimens of subjects with asthma (46). However, in a previous genetic association study, there was no association of genetic polymorphisms in FKBP5 with improved lung function in subjects with asthma treated with inhaled corticosteroids (47). Given its role in glucocorticoid signaling and its reproducible demonstration of induction of expression after inhaled corticosteroid treatment in subjects with asthma, FKBP5 warrants further investigation for its involvement in asthma pathogenesis and treatment response.…”
Section: Original Researchsupporting
confidence: 89%
“…Our data are consistent with those of a meta-analysis performed on patients with mood disorders, in which it was demonstrated that treatment response is associated with FKBP5 gene polymorphism rs4713916, but not with rs3800373 or rs1360780. 31 Similarly, Hawkins et al 32 demonstrated lack of association between rs3800373 and GC response in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Hawkins and colleagues have recently reported that multiple SNPs in stress-induced phosphoprotein 1 (STIP1) were associated with variable FEV 1 responses to treatment with inhaled flunisolide in 382 asthma subjects [59]. This study interrogated SNPs spanning eight candidate genes and identified STIP1 SNPs rs4980524 (intron 1), rs6591838 (intron 1) and rs2236647 (intron 5) affecting percent change in FEV 1 in response to flunisolide at 4 and 8 weeks.…”
Section: Corticosteroidsmentioning
confidence: 95%
“…This study interrogated SNPs spanning eight candidate genes and identified STIP1 SNPs rs4980524 (intron 1), rs6591838 (intron 1) and rs2236647 (intron 5) affecting percent change in FEV 1 in response to flunisolide at 4 and 8 weeks. For example, rs4980524; AA = 5.10 ± 17.16, AC = 5.40 ± 19.00, CC = 11.03 ± 24.03; p = 0.044 at 4 weeks [59]. STIP1 is an adaptor protein that coordinates functions with HSP70 and may be involved in formation of the glucocorticosteroid receptor heterocomplex.…”
Section: Corticosteroidsmentioning
confidence: 99%